Targeting the PANoptosis signaling pathway for myocardial protection: therapeutic potential of Xian Ling Gu Bao capsule - Wu, Xiaoyu; Wei, Jiajia; Zhang, Wenfang; Yi, Yang; Wang, Tingting; Gong, Qihai; Liu, Xin; Li, Haibo; Gao, Jianmei (Frontiers in Pharmacology, 2024)
Myocardial infarction (MI) is a prevalent contributor to global cardiovascular morbidity, characterized by myocardial ischemic injury. PANoptosis, an intricate cellular process, is implicated in the pathogenesis of MI. Xian Ling Gu Bao capsule (XLGB), a traditional Chinese botanical drug remedy containing flavonoids, terpenes, and phenylpropanoids, has various pharmacological properties. However, its specific protective effects on the myocardium after MI are not well understood. Therefore, the present study sought to elucidate the impact of XLGB on MI and its underlying mechanisms. The findings of the study demonstrated that different doses of XLGB had a significant impact on reducing myocardial injury caused by infarction. Notably, the dose of 1000mg/kg XLGB showed superior efficacy compared to the positive control, metoprolol. Furthermore, it was observed that XLGB provided protection to the myocardium against damage induced by MI through the inhibition of PANoptosis. Importantly, the main ingredients of XLGB were found to interact directly with NLRP3/Caspase3/RIP1, a discovery supported by molecular docking and dynamics simulations. This indicates that targeting the NLRP3/Caspase3/RIP1 pathway may offer a therapeutic approach for myocardial protection induced by XLGB. In conclusion, XLGB demonstrates a unique capability in reversing myocardial damage post-MI through its modulation of the NLRP3/Caspase3/RIP1-mediated PANoptosis pathway.